تصميم وإنجاز جهاز قياس الملوحة والعكارة للمياه - بن علي رحيل; فائزي منال (جامعة الشهيد حمه لخضر بالوادي, 2024)
إن الاهتمام بجودة المياه هو استثمار في صحة الإنسان والبيئة التنمية الاقتصادية المستدامة. تحتوي مياه الشرب حول العالم على مجموعة متنوعة من عناصر على شكل أملاح مذابة أو مواد عالقة سواء جاءت هذه المياه المصادر السطحية، أو المياه الجوفية، أو حتى مياه الأمطار. وقد أدى هذا إلى ضرورة الإعداد معايير محددة لقياس وفحص جودة المياه. الآن، مع العلمية و أصبحت التطورات التكنولوجية وأجهزة القياس الإلكترونية والرقمية هي الطريقة المفضلة نظرًا لدقتها ومرونتها وسهولة استخدامها وصيانتها واستبدالها طرق القياس التقليدية. تركيز المواد الصلبة الذائبة الكلية (TDS) و تعد درجة التعكر في الماء من المؤشرات المهمة لتقييم جودة المياه وخصائصها ملاءمة لمختلف الاستخدامات. ولذلك، تم إجراء دراسة شاملة في هذا المشروع ل تصميم وتنفيذ نظام لقياس المواد الصلبة الذائبة الكلية والكثافة التوربينية معًا. في البداية، المفاهيم العامة للمواد الصلبة الذائبة والعكارة وأهميتها تم تقديم قياس لهم. وبعد ذلك تمت برمجة الأوامر المطلوبة باستخدام الأردوينو، وتم تصميم نموذج المحاكاة باستخدام برنامج Proteus، مع إضافة خاصية قياس درجة الحرارة والرطوبة. ثم نتائج TDS والعكارة تم عرض القياسات وتحليلها. تم تأكيد نتائج المحاكاة باستخدام التنفيذ الفعلي للنظام واختباره بأنواع مختلفة من المياه. تم الحصول عليها وأظهرت النتائج تقارب النتائج الفعلية مع نتائج المحاكاة، مع إمكانية ذلك توظيف النظام في المختبرات والتطبيقات الخاصة بمعايرة ومراقبة المياه جودة.Attention to water quality is an investment in human health, the environment, and sustainable economic development. Drinking water around the world contains a variety of elements in the form of dissolved salts or suspended materials, whether this water comes from surface sources, groundwater, or even rainwater. This has led to the necessity of setting specific standards for measuring and examining water quality. Now, with scientific and technological advancements, electronic and digital measuring devices have become the preferred method due to their accuracy, flexibility, and ease of use and maintenance, replacing traditional measurement methods. The concentration of Total Dissolved Solids (TDS) and the degree of t urbidity in water are important indicators for evaluating water quality and its suitability for various uses. Therefore, a comprehensive study was conducted in this project to design and implement a system for measuring the total dissolved solids and turbi dity simultaneously. Initially, the general concepts of TDS and turbidity and the importance of measuring them were presented. Subsequently, the required commands were programmed using Arduino, and the simulation model was designed using Proteus software, adding the feature of measuring temperature and humidity. Then, the results of TDS and turbidity measurements were presented and analyzed. The simulation results were confirmed with the actual implementation of the system and tested with different types of water. The obtained results showed the convergence of actual results with simulation results, with the potential to employ the system in laboratories and applications for calibrating and monitoring water quality.
مذكرات ماستر تخصص هندسة كيميائية
Keywords: الكلمات المفتاحية: المواد الصلبة الذائبة، التعكر، الحساس، الماء، أ rduino.; Keywords: TDS; turbidity; sensor; water; A rduino.